Uncovering mathematical activities and concepts in Batik Pendekar of Madiun City through the lens of ethnomathematics - Ika Krisdiana; Titin Masfingatin; Wasilatul Murtaifiah; Febriana Nor Fadhilla; Gerald DG. Mabuti (Universitas Hamzanwadi, 2025)
Despite the growing recognition of ethnomathematics as a bridge between culture and formal mathematics education, limited research has explored the mathematical knowledge embedded in regional cultural artifacts such as Batik Pendekar from Madiun City, Indonesia. This study aims to uncover the mathematical activities, concepts, and anthropological aspects inherent in the Batik Pendekar tradition to support culturally responsive mathematics education. This research employed a qualitative ethnographic approach. This research was conducted at the Batik Murni Madiun City Gallery by collecting data through observation, interviews, and documentation. The data were analysed qualitatively using triangulation methods. The findings reveal that artisans engage in meaningful mathematical practices, such as measuring fabric dimensions, counting dye usage and production costs, and designing motifs based on geometric principles. The mathematical concepts embedded in Batik Pendekar include geometry, triangular shapes, and transformation geometry (translation and reflection). Additionally, anthropological aspects, such as local wisdom, social values, and symbolic meanings, are integral to these activities. The study concludes that Batik Pendekar serves as a rich ethnomathematical resource, offering opportunities to bridge mathematics learning with local culture and enhance contextual understanding in mathematics education.